Satisfaction of high-level athlete management in universities in Sichuan Province, China / Tang Yudong - Tang , Yudong (2020)
With ongoing development in the construction of high-level sports teams in Chinese universities, the Chinese Ministry of Education is paying more and more attention to the running quality of high-level sports teams in universities. Evaluation of the construction quality of high-level sports teams in universities has received extensive attention from universities and society. However, for various reasons, the main body of high-level sports team evaluation comprises government agencies and universities, and, there is a lack of research on management systems of high-level athletes from the perspective of high-level athletes themselves. Therefore, it is of great theoretical and practical significance to develop a satisfaction model of high-level athlete management systems in Sichuan Province, while conducting empirical analysis from the perspective of high-level athletes. The questionnaire used in this study consists of seven parts: expectations of high-level athletes, perceived management quality, perceived management value, satisfaction of high-level athletes, complaints of high-level athletes, loyalty of high-level athletes, and personal information. A panel of four experts were involved in determining the content validity of the initial questionnaire. Subsequently, five high-level athletes tested the surface validity of the questionnaire to assess whether it was easy to understand. Then, a pilot study was conducted with 83 high-level athletes, testing reliability and validity of the questionnaire, leading to the selection of appropriate items to form a formal questionnaire. In the main study, 327 high-level athletes completed the survey. Smart PLS 3 was used to complete evaluation of the measurement model and the structural model. Main factors affecting satisfaction of high-level athletes with their management systems were found through the application of IPMA. Through IPMA of latent variables of the model, it was found that among the three factors that affect satisfaction, perceived management quality needs to be improved first. However, IPMA based on sub-construction of perceived management quality showed that learning management, and training and competition management were both considered to be of the highest importance, yet were the least satisfactory of the five aspects of perceived management quality, and would need to be improved first. The conclusions of this study found in this study that Sichuan universities should pay attention to evaluation of the satisfaction of high-level athlete management systems. Sichuan universities should begin improving the perception of management quality along with management value of high-level athletes. This should be followed by strengthening the publicity of high-level sports teams; improving the target orientation and expectations of high-level athletes; and improving the evaluation index system of high-level sports teams. The agenda should be to improve the management level of high-level athletes in Sichuan Province universities, thereby effectively improving the satisfaction and loyalty of high-level athletes, and enhancing the competitiveness of high-level sports teams in Sichuan universities.